1967
DOI: 10.1111/j.1469-1809.1967.tb00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Weinberg's differential rule defective ?

Abstract: Summary The Weinberg differential rule seems to be defective in the sense that the found monozygotic twins are less numerous than expected. This study has been supported by grants from the Sigrid Jushlius Foundation. I wish to express my thanks to doctor K. E. Bruun for access to the twin series of the Finnish Foundation for Alcohol Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Some doubts about Weinberg's differential method for estimating the zygosity of twins were raised by findings of placental morphology and genetic characteristics, such as blood type or fingerprint (James, 1971;Myrianthopoulos, 1970;Renkonen, 1967). The main criticism was that the proportion of dizygotic twins was underestimated in Weinberg's assumption, but it is not practicable to attempt a precise diagnosis of zygosity at the time of delivery on a population scale.…”
Section: Discussionmentioning
confidence: 99%
“…Some doubts about Weinberg's differential method for estimating the zygosity of twins were raised by findings of placental morphology and genetic characteristics, such as blood type or fingerprint (James, 1971;Myrianthopoulos, 1970;Renkonen, 1967). The main criticism was that the proportion of dizygotic twins was underestimated in Weinberg's assumption, but it is not practicable to attempt a precise diagnosis of zygosity at the time of delivery on a population scale.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Weinberg's difference rule results in an overestimation of MZ frequencies because of the excess of like-sexed twins in DZ twin maternities [43]. It may easily by seen that the degree of overestimation is proportional to the DZTR, which, in general, has decreased in the period 1960-1984.…”
Section: Estìmation Of Mztrmentioning
confidence: 99%
“…The Weinberg method cannot correct for losses of only one of twins in a gestation, information that is also usually not recorded in birth statistics. It is, therefore, not surprising that the method has often been criticized (e.g., Renkonen 1967 ;and reply by Cannings 1969 ;James 1971James , 1984Keith 1974 ) . Nevertheless, it is a unique and valuable tool to assess the approximate frequency of DZ vs. MZ twins in a population.…”
Section: Multiple Pregnancies 25mentioning
confidence: 96%